Witchcraft, Politics, and Memory in Seventeenth -Century England - Gaskill, Malcolm (The historical journal, 2007)
This article weaves together two episodes separated by a generation. The inciting event is the trial in 1653 of Anne Bodenham, an elderly cunning woman in Salisbury, who found herself embroiled in a feud in a gentry household, set against the turbulent backdrop of a divided city. Her arrest and examination evoked painful memories of an earlier scandal, the fateful association of the duke of Buckingham with Dr John Lambe, a sorcerer whom Bodenham claimed to have served in the 1620s. These tales, in turn, echoed an even older awareness of the perils of the diabolic, most prominently the pact of Dr Faustus. Together these narrative strands demonstrate how feelings of public disgust at Stuart corruption were revived in the commonwealth era and used as a polemical device by puritan activists. Both stories are rich in gossip, rumour, rhymes, libels, anonymous notes, and the practical uses of printed works, not to mention spells and curses, visions and dreams. As such, this article also shows just how complex a witch-trial could be, and serves as a reminder of the sophistication, ingenuity, and ebullience of seventeenth-century communications and consciousness across the social order.